ORGANOLEPTIC QUALITY OF JOPER CHICKEN MEAT GIVEN PINEAPPLE PEEL EXTRACT IN DRINKING WATER - ., Amirullah; Sriyani, N.L.P.; Ariana, I N.T. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aimed to determine the effect of pineapple peel extract ( Ananas comosus (L.) Merr added to drinking water on the organoleptic value of joper chicken meat. This research was carried out at Farm Sesetan, Faculty of Animal Husbandry, Udayana University for 1 month and 2 weeks from September to October 2022. The study also used a Complete Randomized Design (RAL) with 4 treatments and 5 tests assessed by 15 semi-trained panelists. The resulting data were analyzed by non-parametric analysis of Kruskal Wallis and Mann Whitney. The four treatments are: pineapple peel concentration of 0 ml and 1 liter of water as a control (P0), pineapple peel concentration of 60 ml in 1 liter of water (P1), pineapple peel extract concentration of 80 ml in 1 liter of water (P2), pineapple peel extract concentration of 100 ml in 1 liter of water (P3). The variables observed in this study were organoleptic tests which included color, aroma, texture and tenderness, taste and overall acceptance. The results of this study showed that the effect of adding pineapple peel extract ( Ananas comosus (L.) Merr on drinking water had a noticeable effect on the oraganoleptics of joper chicken. The conclusion of this study is the provision of pineapple peel extract with a concentration 10% (P3) through drinking water is most good in improving meat color, meat aroma, texture and tenderness as well as meat flavor.